Unraveling the impact of social media involvement on public health participation in China: mediating roles of social support, social trust, and social responsibility - Wanqi Gong; Xigen Li; Yusi Zhang (Humanities & Social Sciences Communications)
Abstract Public health participation plays a significant role in reducing risks and protecting community members during public health emergencies, especially in China due to its pronounced population density and the imperative for concerted public coordination to achieve the goal of public health protection. Guided by social capital theory and conservation of resources theory, this study develops an analytical model to explore the effect of social media involvement on public health participation mediated by social support, social trust and social responsibility. A cross-sectional survey was executed and a total of 976 completed questionnaires were collected. Results reveal that (a) social media involvement positively predicts social trust, social support and social responsibility; (b) social trust and social support have positive influence on social responsibility and public health participation; (c) further analysis of the data confirms a two-step mediation model: social support and social trust mediate the effect of social media involvement on social responsibility; social responsibility further mediates the relationship between social media involvement, social trust and social support and the outcome variable public health participation. Findings suggest that only in a society with adequate social resources will people take an active part in social actions for common interests. The study extends our understanding of the vital role of social media in maintaining and growing social resources for community health goals.